2016
DOI: 10.1080/00220388.2016.1234036
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Corruption in Business

Abstract: Are women less corrupt in business? We revisit this question using firm-level data from the World Bank's Enterprise Surveys, which measure firms' experience of corruption and the gender of their owners and top managers. We find that women in positions of influence are associated with less corruption: female-owned businesses pay less in bribes and corruption is seen as less of an obstacle in companies where women are represented in top management. By providing evidence that women are, ethically at least, good f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 57 publications
(54 reference statements)
3
40
0
3
Order By: Relevance
“…Other researchers have always adopted a macroeconomic approach, exploring corruption with a specific focus on business contexts. Gillanders and Neselevska (2018) show that experiencing private-to-public bribery reduces trust in large pri- Microeconomic impacts of private-to-public corruption have been discussed less (Badawi & Al Qudah, 2019;Breen et al, 2017;Burnham, Jeon, & Zeng, 2018;Collison, Cobb, Power, & Stevenson, 2008;Putra, Pagalung, & Habbe, 2018;Vu et al, 2018;Wu, 2014). Van Vu et al (2018) shown that the intensity of bribery has a negative impact on firms' financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers have always adopted a macroeconomic approach, exploring corruption with a specific focus on business contexts. Gillanders and Neselevska (2018) show that experiencing private-to-public bribery reduces trust in large pri- Microeconomic impacts of private-to-public corruption have been discussed less (Badawi & Al Qudah, 2019;Breen et al, 2017;Burnham, Jeon, & Zeng, 2018;Collison, Cobb, Power, & Stevenson, 2008;Putra, Pagalung, & Habbe, 2018;Vu et al, 2018;Wu, 2014). Van Vu et al (2018) shown that the intensity of bribery has a negative impact on firms' financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From these results above, we conclude that there is indeed a connection between corruption and innovation in SMCs, but that it may vary depending on the specific aspect that we focus on. For example, the firm's owner has the power to constrain corrupt behaviors, while the top manager may not have as much of an effect unless he/she is an owner, as he/she may be constrained by opposing groups within the corporate structure [35]. In brief, these results offer supports for Hypothesis 1 and may need to be further verified from a gender perspective.…”
Section: The Influence Of Corruption On Smcs' Innovationmentioning
confidence: 49%
“…In line with these studies, female top managers in SMCs are associated with a lower incidence of bribery and a more positive outlook regarding the influence of corruption on doing business. However, female top managers may pose a detrimental effect on SMCs' innovation, because not paying informal money or gifts to a corrupt politician might be seen as threatening to the dominant regime and provoke retaliation [35]. Consequently, these companies supervised by female top managers cannot obtain the extra benefits and resources from political bureaucrats.…”
Section: Feminismmentioning
confidence: 98%
See 2 more Smart Citations